Tourism Marketing Communication Strategy to Increase Tourist Interest in Visiting Pananjung Nature Tourism Park, Pangandaran - Arifda, Jannatinnai’mah; Nugraha, Awaludin; Rizal, Edwin (International Journal of Science and Society, 2025)
Marketing communication strategies are a factor that greatly influences the number of visitors to tourist attractions because they are designed to influence the public to become aware, interested, ultimately visit, and even return for tourists who have already visited. This study aims to identify and formulate tourism marketing strategies at Pananjung Nature Park, Pangandaran. The research method used is descriptive with a qualitative research type and secondary data, particularly from previous literature reviews. The data obtained are explained qualitatively in the form of a detailed and systematic analysis. The research results show that the Pangandaran Regency Youth, Sports, and Tourism Office has implemented integrated tourism marketing communication to promote Pananjung Nature Tourism Park. However, several aspects such as promotion, community-based tourism development, and media are still not optimal. Further development, evaluation, and monitoring are needed in these areas. One aspect that needs to be developed in the long term is the creation of a regional tourism destination brand to enhance the appeal of tourist visits.